Culture, creativity and economy collaborative practices, value creation and spaces of creativity - Hracs, Brian J.; Brydges, Taylor; Haisch, Tina editor; Hauge, Atle; Jansson, Johan; Sjöholm, Jenny (Abingdon, Oxon Routledge, 2022)
This book nuances our understanding of the contemporary creative economy by engaging with a set of three key tensions which emerged over the course of eight European Colloquiums on Culture, Creativity and Economy (CCE): 1) The tension between individual and collaborative creative practices, 2) The tension between tradition and innovation, and 3) The tension between isolated and interconnected spaces of creativity. This book will be of interest to students, scholars and professionals researching the creative economy, as well as specific cultural and creative industries, across the humanities and social sciences"--
Introduction: exploring tensions in the creative economy / Brian J. Hracs, Taylor Brydges, Tina Haisch, Atle Hauge, Johan Jansson and Jenny Sjoholm - - The field of fashion in the digital age: insights from global and 'not-so-global' fashion centres / Taylor Brydges, Marianna D'ovidio, Marianagela Lavanga, Deborah Leslie, Norma M. Rantisi - - Creative splintering and structural change in Leicester, UK / Rachel Granger - -Crowdfunding and co-creation of value: the case of the fashion brand Linjer / Anders Rykkja and Atle Hauge - - Intermediaries, work and creativity in creative and innovative sectors: the case of Berlin / Janet Merkel and Lech Suwala - - Technology as a source for creativity: insights from the Swiss fashion industry / Judith Nyfeler - - Assessing values of cultural heritage and museums: a holistic framework / Vasilis Avdikos and Mina Dragouni - - Spatial processes of translation and how coworking diffused from urban to rural environments: the case of Cowocat in Catalonia, Spain / Ignasi Capdevila - - Cultural intermediaries revisited: lessons from Cape Town, Lagos and Nairobi / Roberta Comunian, Lauren England and Brian J. Hracs - - Curated by pioneers, spaces and resistance: the development of electronic dance music in Stockholm / Johan Jansson and Anna Gavanas.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Cultural industries; Culture -- Economic aspects